Establishment of a transformation protocol for Uganda’s yellow passion fruit using the GUS gene - Tuhaise, Samuel; Nakavuma, Jesca L.; Adriko, John; Ssekatawa, Kenneth; Kiggundu, Andrew (African Journal of Biotechnology, 2019)
Horticulture is one of the fastest growing sectors in Uganda, exporting products worth US$100 million annually. Passion fruit (Passiflora edulis) growing and export is one of the critical contributors to this sector employing over a million farmers. However, a number of biotic and abiotic constraints have initiated widespread enterprise abandonment by farmers. Passiflora improvement efforts by conventional breeding has had limited success calling for research into alternative approaches such as genetic engineering. The study aimed at optimizing existing protocols to develop an efficient and reproducible Agrobacterium mediated transformation system to suit Uganda’s Passiflora cultivars. Agrobacterium tumefaciens strain AGL1 (OD600 of 0.5) harbouring pCAMBIA2301 containing the GUS (uidA) reporter gene was used to infect pre-cultured leaf discs. Leaf discs were then vacuum infiltrated for 1.5 min at 750 mmHg followed by a three day co-cultivation period on MS + acetosyringone (100 μml-1). Putatively transgenic yellow passion fruit shoots were induced on Murashige and Skoog (MS) selection media supplemented with benzylaminopurine (BAP) 8.9 μM, kanamycin (100 mgL-1mgl) and cefotaxime (500 mgL-1). Developed shoots were then transferred to elongation media (MS + 0.44 μM BAP) and later rooted on 5.37 μM naphthaleneacetic acid (NAA). Genetic transformation was monitored using GUS staining. A single independently transformed plant was confirmed by polymerase chain reaction (PCR), translating in a transformation efficiency of 0.456%. A viable in vitro transformation protocol for Uganda’s yellow passion fruit directly from leaf discs was developed using GUS reporter gene. Further investigations are required to improve the reported protocols transformation efficiency.
Keywords: Passion fruit; Passiflora edulis; Passiflora improvement